Evaluation of Costs and Impact of Corporate Social Responsibility (CSR) in the Framework of Triple Bottom Line at PT Terminal Petikemas Surabaya - Taufan Hariono; Driana Leniwati; Nazaruddin Malik (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the implementation of Corporate Social Responsibility (CSR), cost allocation, and its impact on company performance within the framework of the Triple Bottom Line (profit, people, and planet) and evaluate the feasibility of CSR costs using the Cost-Benefit Analysis approach at PT Terminal Petikemas Surabaya. The research method used is a mixed methods approach, namely a qualitative combination through interviews with CSR management, finance sections, HSSE, the community, and community leaders, and quantitative through the analysis of company sustainability report data. The results of the study show that the implementation of CSR is carried out systematically through the stages of social mapping, planning, implementation, and evaluation with a budget allocation of IDR 9.05 billion. CSR has been proven to have a positive impact on the profit aspect through cost efficiency and operational stability, the people aspect through improving community welfare, reducing unemployment, and empowering MSMEs, and the planetary aspect through environmental rehabilitation such as mangrove planting and coastal waste management. In addition, the results of the Cost-Benefit Analysis show that the benefits of CSR are much greater than the costs incurred, resulting in positive net benefits. Thus, CSR not only functions as a corporate social responsibility, but also as a business strategy that supports the company's long-term sustainability.